Perceived Causes of Infertility Among Married Adults in Kwara State, Nigeria - Ariyo, , N. O.,; Alwajud-Adewusi, , M. B.,; Odenike,, A. A.; Gbadamosi, , M. O. (Kashere Journal of Education, 2021)
Infertility is one of the major causes of marital discord with damaging condition that exposes couple to emotional, physical and financial stress. Therefore, this study aimed at investigating the perceived causes of infertility of married adults in Kwara State. The research design adopted for this study is descriptive survey method. The population of this study is all married adults in Kwara State while the target population comprised married adults in the seven selected Local Governments Areas from the three senatorial districts of Kwara State. 420 respondents were selected as the sample for the study. Proportional and simple random sampling techniques were employed by the authors to select the sample for this study. The instrument (questionnaire) used for this study was designed by the authors. Content validity of the instrument was ascertained, and the reliability of the instrument was established using test-retest method. The correlation of the two sets of scores using Pearson’s Product Moment Correlation yielded a co-efficient R=0.81. The data collected was analysed using t-test and Analysis of Variance at 0.05 level of significance. The findings revealed that there were no significant differences on the perceived causes of infertility among married adults in Kwara state on the basis of age and gender. This study, therefore, recommended that Modern and assisted methods of conception such as intra-uterine insemination (IUT), Invitro fertilisation and embryo transfer (IVF/ET), gamete intra fallopian transfer (GIFT) should be encouraged by medical personnel and implemented by couples suffering from infertility. Counselling services should be organised regularly for couples to alleviate the impacts of infertility on the well-being of the couple.